The Nile River and the Grand Ethiopian Renaissance Dam - Elghouty, Amal Soliman; Ali, Dina; Ayman, Rawand (Archives of Business Research, 2022)
Scarcity of freshwater supplies is rapidly becoming an important factor in reducing regional growth and creating tension among regions with the same water resources. The main concern of the paper is to clarify the extent of the problems and tensions between Egypt and Ethiopia regarding the construction of the Grand Renaissance Ethiopian Dam. In the paper, some facts regarding the previous agreements and tensions between the two countries will be discussed. Some recommendations for policymakers will be presented in the last section.